2021
DOI: 10.3389/fcell.2021.714330
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Low-Density Lipoprotein Receptor-Related Protein LRP6 and Its Association With Disease: Wnt/β-Catenin Signaling and Beyond

Abstract: Wnt signaling plays crucial roles in development and tissue homeostasis, and its dysregulation leads to various diseases, notably cancer. Wnt/β-catenin signaling is initiated when the glycoprotein Wnt binds to and forms a ternary complex with the Frizzled and low-density lipoprotein receptor-related protein 5/6 (LRP5/6). Despite being identified as a Wnt co-receptor over 20 years ago, the molecular mechanisms governing how LRP6 senses Wnt and transduces downstream signaling cascades are still being deciphered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 142 publications
(190 reference statements)
1
18
0
Order By: Relevance
“…It has been well known that mutation or dysregulation of LRP6 proteins is directly associated with oxidative stress, dyslipidemia, atherosclerosis, and coronary artery disease [ 19 21 ]. Caspase-3 activities were enormously increased in 18-hour H/R-exposed HUVECs but remarkably reduced after transfection with mimic-126.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that mutation or dysregulation of LRP6 proteins is directly associated with oxidative stress, dyslipidemia, atherosclerosis, and coronary artery disease [ 19 21 ]. Caspase-3 activities were enormously increased in 18-hour H/R-exposed HUVECs but remarkably reduced after transfection with mimic-126.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well established that LRP6 regulates breast cancer. LRP6’s expression is most often up-regulated in breast cancer tissue, and overexpression or knockdown of LRP6 causes or halts breast tumorigenesis ( 135 ). In line with the study conducted in RB, the expression of LRP6 in the form of a ceRNA axis also experiences an increase in expression, and in the direction of RB development, this increase in expression demonstrates its oncogenic effects ( 30 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…LRP6, a member of the LDLR gene family, is a co-receptor of Wnt, and the internalization of LRP6 can lead to the inhibition of Wnt/β-catenin signaling pathway ( 30 ). In addition, in hyperlipidemia rat model hyperlipidemia could inhibit dishevelled-2 expression and its phosphorylation, thus inhibiting Wnt/β-catenin signaling pathway ( 31 ). Consistently, the present study found that a low LDL-C/Apo B ratio was an independent contributor to low bone turnover in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%